The Effect of Differences In Etefon Concentrations On The Level of Riteness And Quality of Melon (Cucumis Melo L.) - Nugrah Fahera; Rismawati; Dodi Budirokhman (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2025)
Melons (Cucumis melo L.) are a high-value horticultural commodity that faces challenges in terms of irregular ripening, especially in the Cirebon area and its surroundings. This study aims to evaluate the effect of different concentrations of the growth regulator ethephon on the acceleration of ripening and melon fruit quality. The study was conducted using a completely randomized design with six levels of ethephon concentration (0, 25 ml/L, 50 ml/L, 75 ml/L, 100 ml/L, and 125 ml/L) applied to post-harvest melons, and observations were made on days 2, 4, and 6 of storage. The parameters observed included weight loss, total soluble solids, vitamin C, chlorophyll, anthocyanin, and carotenoids. Meanwhile, the organoleptic test was conducted subjectively using human senses as the primary assessment tool. The results showed that the 75 mL/L concentration provided the best effect on ripening acceleration, as indicated by increased anthocyanin, chlorophyll degradation, and softer fruit texture, as well as high panelist preference. Although the 50 mL/L concentration showed the highest taste and total soluble solids, the optimal quality characteristics were found at 75 mL/L. It is recommended to use ethephon at a concentration of 75 mL/L to accelerate ripening while maintaining optimal melon fruit quality during storage.